Role of metabolites in mediating the effect of triacylglycerol on aplastic anemia - Jingkui Zhu; Wen Li (Hematology)
Background Observational studies have found a link between lipid metabolism disorders and aplastic anemia (AA). However, due to confounding variables and reverse causation, it is difficult to conclude such a causal link. The precise mechanism and potential implications of lipid metabolism disorder in AA remain unclear, necessitating further studies in this area.Method This study aimed to examine the causal relationship between 38 different subtypes of triacylglycerols and AA using two-sample Mendelian randomization (MR). Additionally, two-step MR analyses were conducted to investigate the mediating effects of vitamin A to oleoyl-linoleoyl-glycerol (18:1–18:2) ratio.Results MR analysis showed that triacylglycerol (53:3) levels were positively associated with the risk of AA [inverse variance weighting (IVW): odds ratio (OR) = 1.131,95% confidence interval (CI):1.029-1.243, P = 0.011; Bayesian weighted MR (BWMR): OR = 1.137,95% CI:1.031-1.254, P = 0.010]. Triacylglycerol (53:3) level showed no inverse causality with AA (IVW:P = 0.834; BWMR:P = 0.349). Mediation analyses showed that increasing the vitamin A to oleoyl-linoleoyl-glycerol (18:1–18:2) ratio can decrease the risk of AA.Conclusion This study revealed the association between vitamin A to oleoyl-linoleoyl-glycerol (18:1–18:2) ratio, triacylglycerol (53:3) levels and AA, and indicated that lowering triacylglycerol (53:3) levels can reduce the risk of AA.